Why won't they sit with me? An exploratory investigation of stereotyped cues, social exclusion, and the P3b. (3rd September 2017) - Kiat, John E.; Straley, Elizabeth; Cheadle, Jacob E.
ABSTRACT: The importance of understanding how we anticipate and prepare for being socially excluded is underscored by the numerous adverse mental and physical consequences of social rejection. In this study, we adapted a social exclusion paradigm, the Lunchroom task, to investigate the use of social context cues in the formation of social outcome expectations as indexed by the P3b, an ERP component associated with attention orientation and context updating. In this task, Black and White participants were presented with either neutral or stereotyped cues prior to being exposed to simulated inclusion versus exclusion outcome scenarios. Black participants showed evidence of (1) a significantly reduced P3b response to exclusions preceded by stereotyped cues relative to neutral cue-related exclusions and (2) a marginally significant increase in the P3b response to inclusions relative to exclusions when both were preceded by stereotyped cues. Both of these findings suggest a key role for the use of social cues in the formation of outcome expectations. In line with our hypothesis that the random intermixing of inclusion and exclusion outcomes would prevent formation of outcome expectations when coupled with the absence of self-relevant cues, no overall P3b modulations were observed among a comparison group of White participants.